Japan's Imperial Army : Its Rise and Fall, 1853 - 1945 - Drea, Edward J., 1944- (Book collections on Project MUSE., 2009)
This book looks well past the stereotypes of suicidal banzai charges and fanatical leaders blindly devoted to their emperor to the more complex story of how that army came to power and extended its influence at home as well as abroad to become one of the world's dominant fighting forces. The author traces the Japanese army's origins, evolution, and impact as an engine of the country's regional along with global ambitions from mid-19th century incursions through the end of World War II. Encompassing doctrine, strategy, weaponry, and civil-military relations, this study also captures the dominant personalities who shaped the Imperial Army, from Yamagata Aritomo-- an incisive geopolitical strategist-- to Anami Korechika-- who exhorted the troops to fight to the death during the final days of World War II. Summing up, the author suggests that an army that places itself above its nation's interests is doomed to failure.